Posterior reversible encephalopathy syndrome: associated clinical and radiologic findings: a study from tertiary care hospital - Mahabalshetti, Amrut; Patil, Preetam B.; M., Dhananjaya (International Journal of Research in Medical Sciences, 2016)
Background: Posterior reversible encephalopathy syndrome (PRES) is a syndrome with neuroimaging findings of reversible vasogenic subcortical edema without infraction. It is potentially reversible clinico-neuro-radiological syndrome featured by clinical symptoms of headache, altered mental status and seizures, visual perception defects in collaboration with radiological findings of posterior cerebral edema appearing as hypodense area on MRI and can also involve the brain stem, cerebellum and other cerebral areas. To identify the clinical associations and radiologic findings of posterior reversible encephalopathy syndrome (PRES). Methods: One hundred twenty patients were included in the study. Demographic data, clinical history, blood pressure measurements, laboratory investigations, predisposing condition and neuroimaging were assessed. The primary etiology of PRES was determined for each case on the basis of the diagnosis of the attending clinician/s. Results: Out of the one hundred twenty retrospectively identified cases, 98 were females and 22 were males. Mean age of the patients at presentation was 28.94 years. The most common clinical presentation was seizures, seen in 94 patients (78.3%). The most common location was the parieto-occipital 69 (57.5%), followed by temporal lobe 19 (15.8%), frontal lobe 14 (11.6%) and basal ganglia 08 (6.6%). Conclusions: PRES is an under diagnosed condition, needs high degree of suspicion for diagnosis. In this study females are commonly affected, and most of them were in postpartum period and had good prognosis.